2015
DOI: 10.1542/hpeds.2015-0100
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effectiveness of Oral Versus Outpatient Parenteral Antibiotic Therapy for Empyema

Abstract: The frequency of complications was similar with oral therapy and OPAT for children with PPE. Oral antibiotics may be considered safe and effective for children with PPE who will be discharged to complete therapy in the outpatient setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 29 publications
2
12
1
Order By: Relevance
“…The findings are consistent with those of a previous retrospective study that showed that oral route is as effective as intravenous route for completing the course of antibiotic therapy in children treated for complicated pneumonia,4 and also corroborate those of another study (by same group of authors) that showed no difference in treatment failure rates between groups (intravenous vs oral therapy) for children treated for acute osteomyelitis 5. However, there are some limitations in this study.…”
Section: Commentarysupporting
confidence: 92%
“…The findings are consistent with those of a previous retrospective study that showed that oral route is as effective as intravenous route for completing the course of antibiotic therapy in children treated for complicated pneumonia,4 and also corroborate those of another study (by same group of authors) that showed no difference in treatment failure rates between groups (intravenous vs oral therapy) for children treated for acute osteomyelitis 5. However, there are some limitations in this study.…”
Section: Commentarysupporting
confidence: 92%
“…Prolonged antimicrobial therapy is warranted, irrespective of additive treatment modalities such as video-assisted thoracoscopic surgery (VATS) or fibrinolysis. A retrospective study comparing outpatient IV versus oral treatment did not show differences in outcome, thus promoting oral treatment [74]. This was confirmed by another retrospective cohort study evaluating 2132 children with empyema.…”
Section: Pleural Empyemamentioning
confidence: 71%
“…1 Only 1 single-center study has addressed the effectiveness of PICC compared with oral antibiotic therapy in children with complicated pneumonia. 11 Our objectives were to compare the effectiveness of postdischarge oral versus intravenous antibiotics delivered via a PICC for children with complicated pneumonia and to determine differences in treatmentrelated complications.…”
mentioning
confidence: 99%